Parietal Cell Antibodies in Type 1 Diabetes Mellitus and Its Implications for Iron Deficiency: A Tertiary Centre Experience from North India - Khurshid A. Bhat; Sonali Verma; Eesh Bhatia; Vijayalakshmi Bhatia; Siddhnath Sudhanshu (Indian Journal of Endocrinology and Metabolism)
Introduction: Parietal cell antibody (PCA)-mediated auto-immune gastritis is known to increase the risk of iron-deficiency and pernicious anaemia in adults with type 1 diabetes mellitus. However, in children and young adults with type 1 diabetes, these data are scarce. We aimed to study the prevalence of parietal cell antibodies (PCAs) and its clinical associations in people with type 1 diabetes with onset below 30 years. Methods: In a cross-sectional study, 224 children and young adults with type 1 diabetes and 171 healthy controls were enrolled. We measured haemoglobin, serum ferritin, vitamin B12, PCA, thyroid peroxidase, and anti-tissue transglutaminase antibodies in all patients. Mann–Whitney U test for continuous data and Chi square test for categorical data were used. Linear regression analysis was performed with haemoglobin as a dependent variable. Results: The prevalence of PCA was significantly higher in patients than in controls (22% vs 10.2%; P = 0.002). Patients with PCA had a higher frequency of anaemia (60% vs 30%, P < 0.001), lower haemoglobin [7.3 (1.6) vs 7.8 (1.1) mmol/L; P = 0.002], and lower serum ferritin [46.9 (70.8) pmol/L vs 66.0 (105.3) pmol/L; P = 0.04], as compared to those without PCA. On multivariate analysis, haemoglobin was associated with PCA (β = -0.174, P = 0.005) and serum ferritin (β =0.247, P < 0.001). Conclusion: Presence of PCA was an independent risk factor for iron deficiency and anaemia in children and young adults with type 1 diabetes.